Effect of UV exposure on indium oxide thin film transistors - Kok, Lendl Yi Zhi (2016)
Amorphous oxide semiconductors are of research interests recently as it has the ability to be adapted into various manufacturing methods, and produced at a lower cost as compared to conventional silicon semiconductors. Solution process deposition method is one of the methods to produce amorphous oxide semiconductors. Solution process is favoured over vacuum deposition techniques as it deposits thin films at a lower temperature and it allows the deposition on flexible substrates, forming flexible electronics. However one major hurdle is that all processes need to undergo a post-deposition thermal annealing in order to drive condensation and densification of oxide layers. This thermal annealing step often takes place at 250C or higher temperatures, and this hinders the ability to use flexible substrates such as PET and other polymers with low glass transition temperatures. Hence, there is a need to look into alternative post deposition methods that can take place at a much lower temperature to enable the use of flexible substrates. One of these alternative methods is UV exposure and the main purpose of this study is to look into the effects of UV exposure on indium oxide thin film transistors and compare them to the conventional thermal annealing method. Various electrical parameters of the indium oxide thin film transistors are mainly studied such as the saturation mobility, sub-threshold swing, threshold voltage, and On/Off ratio. Devices made were also studied with various characterization techniques such as optical absorption spectroscopy, Fourier Transform Infrared spectroscopy, X-ray diffraction, Atomic Force Microscopy, and X-ray Photoelectron Spectroscopy. The results show that UV exposed devices showed a peak saturation mobility of 34.44 cm^2/Vs while thermal annealed samples only showed 1.21 cm^2/Vs. This significant higher saturation mobility translates into higher device performance as compared to thermally annealed devices. However there is also a drawback for UV exposed devices as they exhibited poorer sub-threshold swing of 0.93 V/dec while thermal annealed samples showed 0.58 V/dec. With the use of FTIR spectroscopy, it was found that UV exposure also removes more impurities from the oxide layer. With the aid of XPS, this was further verified and the reduction of impurities led to the formation of better In-O-In layer, explaining the phenomenon of increased mobility. On the other hand, the high penetration power also damages the semiconductor-dielectric interface which results in the increase in sub-threshold swing. The drawbacks of UV exposure are minimal compared to the significant increase in saturation mobility therefore it demonstrates that UV exposure has great potential in replacing thermal annealing as the low temperature post deposition treatment technique.